LANGUAGE EDUCATION IN THE CONDITIONS OF EUROPEAN INTEGRATION PROCESSES - V.A. Hamanyuk (Academy of Cognitive and Natural Sciences, 2010)
The article deals with influence of integration and globalization processes on the role offoreign languages and methods of their studying in European countries.